2022
DOI: 10.1111/mec.16458
|View full text |Cite
|
Sign up to set email alerts
|

Genetic composition and diversity of Arabica coffee in the crop’s centre of origin and its impact on four major fungal diseases

Abstract: Conventional wisdom states that genetic variation reduces disease levels in plant populations.Nevertheless, crop species have been subject to a gradual loss of genetic variation through selection for specific traits during breeding, thereby increasing their vulnerability to biotic stresses such as pathogens. We explored how genetic variation in Arabica coffee sites in southwestern Ethiopia was related to the incidence of four major fungal diseases. Sixty sites were selected along a gradient of management inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 148 publications
(270 reference statements)
0
8
2
Order By: Relevance
“…However, a recent study in our region did not find an effect of genetic diversity on coffee diseases (Zewdie et al, 2023).…”
Section: (D)contrasting
confidence: 80%
See 1 more Smart Citation
“…However, a recent study in our region did not find an effect of genetic diversity on coffee diseases (Zewdie et al, 2023).…”
Section: (D)contrasting
confidence: 80%
“…While these cultivars were selected for resistance to coffee berry disease caused by Colletotrichum kahawae , and are not known (nor believed) to be more susceptible to insect pests, the genetic uniformity in the plantation system may favour the adaptation of insects to the crop. However, a recent study in our region did not find an effect of genetic diversity on coffee diseases (Zewdie et al, 2023).…”
Section: Discussioncontrasting
confidence: 56%
“…Population genetics predicts that diseases should be less frequent in populations of hosts with higher levels of genetic diversity. Genotyping‐by‐sequencing in Arabica coffee sites in southwestern Ethiopia showed that genetic diversity in coffee trees was higher in less managed sites and the incidence of four major fungal diseases was related to the genetic composition of the coffee stands (Zewdie et al, 2023). Genetic diversity in coffee trees was also related to the within‐site variation of coffee berry disease, but not to the mean incidence of any of the four studied diseases across sites (Zewdie et al, 2023).…”
Section: Fungal Crop Pathogensmentioning
confidence: 99%
“…These 21 papers focus on various types of microbial diversity, including domesticates, pathogens, and host‐associated microbiota, using a range of methodologies including population and evolutionary genomics, metagenomics, and field and laboratory experiments. As a whole, the papers address a few main subjects: domesticated microorganisms and microorganisms thriving in anthropogenic environments (Harrouard et al., 2023; Silva et al., 2023; von Gastrow et al., 2023), fungal pathogens (Ali et al., 2023; Louet et al., 2023; Rogério et al., 2023; Saubin et al., 2023; Stalder et al., 2023; Wang et al., 2023; Zewdie et al., 2023), metagenomics and microbiomes of animals and human (Bischofberger & Hall, 2023; Corsi et al., 2023; Mac Alpine et al., 2023; Moeller, 2023; Pedro et al., 2023; Peimbert & Alcaraz, 2023; Tessandier et al., 2023; Yuan et al., 2023), and metagenomics and microbiomes of crops (Gao et al., 2023; Richard et al., 2023). Collectively the articles in this Special Issue ‘underline the huge impact of the anthropogenic environment in microbial evolution, including the emergence and spread of pathogens as well as the benefits provided by domesticated or mutualistic fungi and bacteria’ (Giraud et al., 2023).…”
Section: Highlights Of 2023mentioning
confidence: 99%
“…Rogério et al, 2023;Saubin et al, 2023;Stalder et al, 2023;Wang et al, 2023;Zewdie et al, 2023), metagenomics and microbiomes of animals and human(Bischofberger & Hall, 2023;Corsi et al, 2023;Mac Alpine et al, 2023;Moeller, 2023;Pedro et al, 2023;Peimbert & Alcaraz, 2023;Tessandier et al, 2023;Yuan et al, 2023), and metagenomics and microbiomes of crops(Gao et al, 2023;Richard et al, 2023). Collectively the articles in this Special Issue 'underline the huge impact of the anthropogenic environment in microbial evolution, including the emergence and spread of pathogens as well as the benefits provided by domesticated or mutualistic fungi and bacteria'(Giraud et al, 2023).Finally, our third Special Issue, Insights into Ecological & Evolutionary Processes via Community Metabarcoding includes 'papers that highlight the power of high-throughput sequencing (HTS) data to address classic questions in ecology and evolution, particularly focused on metabarcoding (amplicon) datasets in conjunction with complementary -omics data types and/or models/theory to infer overall ecosystem processes'(Gillespie et al, 2023).…”
mentioning
confidence: 99%